2-Amino-5-methylpyridinium 3-aminobenzoate - Hemamalini, Madhukar (International Union of Crystallography, 2010)
In the title compound, C(6)H(9)N(2) (+)·C(7)H(6)NO(2) (−), the H atom of the N—H group and an H atom of the 2-amino group from the cation are involved in intermolecular N—H⋯O hydrogen bonds with the O atoms of the carboxylate group of the anion, forming an R (2) (2)(8) ring motif. These ring motifs are, in turn, connected by further N—H⋯O hydrogen bonds, forming a two-dimensional network. The crystal structure is further stabilized by π⋯π stacking interactions involving the benzene and pyridinium rings with a centroid–centroid distance of 3.7594 (8) Å.